Analisis Yuridis Andil Tanggung Jawab Notaris atas Akta Pendirian Perseroan Terbatas dengan Data Palsu - Diva Rayhan Reydoza; Febri Melia Andini; Imanuel La Antrag; Sintong Arion Hutapea (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
Notaries have a crucial role in making the deed of establishment of a limited liability company which is the basis for the existence of a legal entity. However, in practice, deeds containing false data are often found, causing legal problems related to the liability of the parties involved. This research aims to analyse the application of the piercing the corporate veil doctrine to limited liability companies established with false data as well as the notary's responsibility in such cases. The research method used is normative legal research with statutory and conceptual approaches. The results show that the doctrine of piercing the corporate veil can be applied when there is evidence of abuse of the legal entity, so that the responsibility shifts to the owner or management. In addition, notaries who are negligent or intentionally allow forgery can be held civil, administrative, and criminal liabilities. Therefore, notaries must apply the precautionary principle in making deeds to avoid legal consequences.